Digital poster-assisted project-based learning: enhancing creativity and learning engagement in pancasila education - Normayanti Normayanti; Al Rafni; Junaidi Indrawadi; Fatmariza Fatmariza (Journal of Educational and Learning Studies, 2026)
This study aimed to examine the effectiveness of digital poster-assisted Project-Based Learning (PjBL) in improving students' creativity and learning engagement in Pancasila Education. A quantitative quasi-experimental design with a nonequivalent control group was employed involving 68 tenth-grade students, equally assigned to experimental and control groups. Data were collected through observation sheets and essay tests and analyzed using paired-samples t-test, independent-samples t-test, normalized gain (N-Gain), and Multivariate Analysis of Variance (MANOVA). The experimental group achieved significantly higher creativity (t = 14.662, p < 0.001) and learning engagement (t = 13.139, p < 0.001) than the control group. Moderate N-Gain scores were obtained for creativity (60.65%) and learning engagement (59.46%), compared with 14.43% and 15.57% in the control group. MANOVA further confirmed a significant simultaneous effect of digital poster-assisted PjBL on both variables (Wilks' Lambda = 0.158, F = 173.150, p < 0.001), with large effect sizes for creativity (η² = 0.765) and learning engagement (η² = 0.723). Digital poster-assisted PjBL is an effective student-centered instructional approach for enhancing creativity and learning engagement while supporting the development of twenty-first-century competencies in Pancasila Education